Bernard–Soulier Syndrome: A Review of Epidemiology, Molecular Pathology, Clinical Features, Laboratory Diagnosis, and Therapeutic Management - Kaya, Zühre (Seminars in Thrombosis and Hemostasis, 2024)
Bernard–Soulier syndrome (BSS) is an inherited platelet function disorder caused by mutations in the genes that encode the glycoprotein (GP) Ibα and GPIbβ subunits, as well as the GPIX subunit in the GPIbIX complex, which is located on the platelet surface and has roles in platelet adhesion and activation. Patients with autosomal recessively inherited biallelic BSS have a homozygous or compound heterozygous expression in the GPIbα, GPIbβ, and GPIX subunits of the GPIbIX complex. Patients with autosomal dominantly inherited monoallelic BSS have a heterozygous expression in only the GPIbα and GPIbβ subunits of the GPIbIX complex. To date, no BSS mutations in the GP5 gene have been reported. Patients with biallelic form are usually diagnosed at a young age, typically with mucocutaneous bleeding, whereas monoallelic forms are generally identified later in life and are frequently misdiagnosed with immune thrombocytopenic purpura (ITP). In biallelic BSS, giant platelets in the peripheral blood smear, absence of ristocetin-induced platelet aggregation (RIPA) using light transmission aggregometry (LTA), and complete loss of GPIbIX complex in flow cytometry are observed, whereas in monoallelic forms, genetic diagnosis is recommended due to the presence of large platelets in the peripheral blood smear, decreased or normal RIPA response in LTA, and partial loss or normal GPIbIX complex in flow cytometry. Platelet transfusion is the main therapy but recombinant factor VIIa is advised in alloimmunized patients, and allogeneic stem cell transplantation is suggested in refractory cases. Antifibrinolytics and oral contraceptives are utilized as supplementary treatments. Finally, differentiation from ITP is critical due to differences in management. Thus, BSS should be kept in mind in the presence of individuals with chronic persistent thrombocytopenia, positive family history, unresponsive ITP treatment, macrothrombocytopenia, and absence of RIPA response.
Keywords: biallelic; monoallelic; Bernard–Soulier syndrome; immune thrombocytopenic purpura